Evaluation of a Novel Bone Substitute Injection Technique for Potential Treatment of Impact Injury to the Equine Palmar Metacarpal Condyle - Rice, Hilary C.; Brokken, Matthew T.; Hostnik, Eric T.; Bertone, Alicia L. (Veterinary and Comparative Orthopaedics and Traumatology, 2019)
Objective The aim of this study was to evaluate the injection of a bone substitute material (BSM) into an impact lesion in the palmar condyle of the third metacarpal bone.Study Design This was an in vivo controlled study performed on six horses.Materials and Methods Medial metacarpal condyles were exposed via arthrotomy and a compressive lesion created in anaesthetized horses using 80 psi (27.6 MPa) onto the articular surface (n = 12). Paired limbs were randomly selected as a control or for extra-articular injection of BSM towards the subchondral bone near the compressive lesion. Parameters of the surgical techniques and BSM distribution outcomes were evaluated using magnetic resonance imaging analysis, histology and histomorphometry.Results Injection of the BSM required significant pressure, as well as the use of a pilot hole. The BSM was visible in all magnetic resonance imagings in treatment limbs. Post-impact treatment limbs had greater average grey scale values than controls (p = 0.041), and greater average grey scale values than pre-impact treatment limbs (p = 0.004). Histology demonstrated haemorrhage and microfractures at the site of compression with no evidence of bone disruption from BSM injection.Conclusion Injection of BSM into the dense subchondral bone of the equine palmar condyle could be targeted to a site of injury, distributed subchondrally and without further injury to bone or cartilage.Clinical Significance This procedure has potential for the treatment of clinical impact injury or osteoarthritis in horses, and long-term studies are warranted.
Keywords: subchondral bone; subchondroplasty; osteoarthritis; atheletes; impact injury